Rule violations as a casue of injuries in male Norwegian professional football - Andersen, T. E.; Engebretsen, L.; Bahr, R. (The American Journal of Sports Medicine, 2004)
BACKGROUND: Foul play is an important cause of injury in football. Reduction of foul play and adherence to the laws of the game may be possible interventions to reduce the rate of injuries. PURPOSE: To evaluate how violations of the laws of the game contribute to injury and to investigate whether the decisions made by the referees are correct in high-risk situations. STUDY DESIGN: Prospective cohort study. METHODS: Videotapes and injury information were collected for 174 of 182 matches from the male Norwegian professional league during the 2000 season. Three Norwegian FIFA referees performed retrospective blinded evaluation of the 406 incidents. RESULTS: Less than one-third of the injuries identified on video and about 40% of the incidents with a high risk of injury resulted in a free kick being awarded. About 1 in 10 of these situations led to either a yellow or red card. The agreement between decisions made by the match referee and the expert referee panel was good, that is, their decisions agreed in 85% of the situations in which injury occurred. CONCLUSIONS: There may be a need for an improvement of the laws of the game of football to protect players from dangerous play.